MEMBANGUN KOMUNITAS YANG KREDIBEL: KOMITMEN TERHADAP INSTITUSI SEBAGAI PRASYARAT MENUJU KOMUNITAS KEAMANAN ASEAN 2015 - Mohamad Rosyidin (Jurnal Universitas Paramadina, 2013)
AbstractASEAN is not ready to be a “security community” in the region despite itsclaim as a “pluralistic security community”. ASEAN dispute settlementmechanism such as the TAC, the ARF, and the ASEAN High Council havelost its legitimacy because there has been less political will from ASEANmember states to use them. While there is reluctance, ASEAN have creatednew form of institution called AIPR. Instead of using any of thoseinstitutions, ASEAN relied on external power such as UNSC, ICJ, and OIC.Traditional dispute settlement which emphasizes on bilateral mechanismrather than multilateral one has also weakened existing frameworks theyhave. The aim of this article is to describe the institutional problemsembedded in the creation of ASEAN Security Community. Usingconstructivism in International Relations, this article emphasizes on normsand identity relation. This article claims that in order to shape collectiveidentity, ASEAN member states should build mutual trust by returning totheir genuine institutions of conflict resolution. Because the management ofinternal disputes settlement among member states is the core of securitycommunity idea, their commitment to institutions mentioned above willdetermine whether or not ASEAN is ready to be a security community. Ifthey failed to conform norms, they would have no capacity to build a sense ofcommunity. If they have no sense of community, they would have nocommunity at all.